Fluorescence Properties of Novel Multiresonant Indolocarbazole Derivatives for Deep-Blue OLEDs from Multiscale Computer Modelling - Nikita O. Dubinets; Andrey Yu. Sosorev (Molecules)
Multiresonant fluorophores are a novel class of organic luminophores with a narrow emission spectrum. They can yield organic light-emitting devices, e.g., OLEDs, with high colour purity. In this study, we applied DFT and multiscale modelling to predict the electronic and optical properties of several novel derivatives of indolocarbazole pSFIAc, which had recently shown a high potential in deep-blue OLEDs. We found that the addition of phenyls to a certain position of the pSFIAc core can considerably increase the fluorescent rate, leaving other properties (HOMO, LUMO, lowest excited singlet and lowest triplet states’ energies) virtually unaffected. This can improve the efficiency and stability of deep-blue organic light-emitting devices; the suggested phenyl-substituted indolocarbazoles have been shown to be compatible with two popular anthracene-based hosts. On the contrary, the addition of phenyls to another positions of the core is detrimental for optoelectronic properties. QM/MM and QM/EFP calculations yielded negligible inhomogeneous broadening of the emission spectrum of the studied luminophores when embedded as dopants in anthracene-based hosts, predicting high colour purity of the corresponding devices. On the basis of the obtained results, we selected one novel multiresonant indolocarbazole derivative that is most promising for organic light-emitting devices. We anticipate the revealed structure-property relationships will facilitate the rational design of efficient materials for organic (opto)electronics.